Clinical and epidemiological profile of patients who seek post-exposure prophylaxis after sexual exposure to HIV and their adherence to the medication regimen in a specialized center in Cascavel, Paraná, Brazil - Orlandi, Vania; Fronza, Dilson; Gomes, Douglas Soltau; Horvath, Josana Aparecida Dranka; Yonegura, Winny Hirome Takahashi (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Post-Exposure Prophylaxis (PEP) is part of a new strategy for the prevention of Human Immunodeficiency Virus transmission adopted by the Brazilian Ministry of Health. The approach involves the use of antiretroviral medication for 28 days after potential exposure to HIV in order to prevent the establishment of infection. Objective: To evaluate the epidemiological profile of patients who seek PEP after consensual sexual activity in a specialized center for infectious diseases in Cascavel, Paraná, Brazil. Methods: This study involved retrospectively evaluating a cohort based on the medical records of patients who received PEP between November 2011 and July 2016. Results: A total of 153 medical records were analyzed and it was observed that more men (77.12%) than women (22.9%) sought PEP. The average age of women and men was 30.05 years and 29.06 years, respectively. Since the implementation of PEP in 2001, the annual demand for the treatment has steadily increased. The majority of patients (96.76%) sought care within the 72-hour deadline for the start of prophylaxis. Although 85.62% of total cases received recommendations for the use of prophylaxis, it was possible to verify adherence to the medication regimen for the recommended time in only 45.90% of cases. Among the patients who adhered to treatment, no cases of seroconversion were observed. A gradual decrease in attendance of follow-up appointments was noted, with approximately 45% of patients abstaining after 30 days of initial care, increasing to nearly 80% after 12 weeks. Conclusion: Despite the apparent efficacy of prophylaxis, keeping track of patients undergoing prophylactic treatment remains difficult. Improved knowledge on the epidemiological profile of the population in question may be expected to guide public policies aimed at the prevention of Acquired Immunodeficiency Syndrome.